Change Health Analysis: A Framework for Evaluating the Readiness and Integration of Change Enablers - Tourista, Meiko; Sutanto, Eddi; Azwir, Akbar (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
- The successful delivery of organizational change is an inherently complex endeavor, determined overwhelmingly by the readiness and ability of the human capital to adopt new ways of working. High-profile studies consistently indicate that the primary driver of change failure is the inadequate management of the